“evaluación de la seguridad e impacto ambiental en la ejecución de proyectos en una empresa de servicios generales” - Aldave Ruiz Cesar Enrique, Cesar Enrique (2016)
This work has been developed in order to describe the activities I've been doing in various companies in the field of Civil Construction, in my capacity as Safety Supervisor. In chapter I the generalities of the company is described, the vision, mission and principles of the CHIMU CONTRATISTAS GENERALES S.A. company has been taken as a reference. In chapter II the executive experience of CHIMU CONTRATISTAS GENERALES S.A. is detailed, demonstrating the importance of Safety and the Environmental Impact Studies affecting the project implementation. In chapter III is described the theoretical basis about Safety activities carried out in construction companies as well as environmental aspects. In chapter IV the environmental impact of the project implementation is assessed: "Rehabilitation of intake weir, prosecution and coating of the spillway drain channel of Pomabamba Hydroelectric Plant", whereby is illustrated the way how is filled out the evaluation tables. In chapter V the conclusions and final recommendations of the undertaken activities are given.